Pertanggungjawaban Pidana Terhadap Anak di Bawah Umur Pelaku Kecelakaan Lalu Lintas yang Mengakibatkan Kematian - Aldo Fahrezi Raja Muda Lubis; Alpi Sahari; Surya Perdana (Universitas Medan Area, 2020)
Traffic accidents are events that are not intended to be expected and are expected to be used in the way of law and forms of legal action and human rights. Based on the results of the study, it was found that in the determination of the provisions and the portion of the traffic accident accidents which resulted in the loss of others most of the traffic accidents caused the loss of someone involving someone as the culprit, the judge was decided through restorative justice through the university. Another verdict handed down by the judge is the trial and trial of the victims of traffic accidents that cause the loss of lives of others. That the protection of the law confronts the victim of a traffic accident that causes the death of another person through the universe. This is based on the provisions of Law No. 11 of 2012 in Article 2 in the implementation of the Criminal Justice System for Children and the children, based on the basis of protection, justice, non-discrimination, the importance of the best part, the appreciation of the needs of the part, the survival and development of the children, guidance and guidance of the ministry, the promotion and the promotion of the sector, the promotion and the guidance of the civil society, the promotion and promotion.